Business Regulation in South Asia and the Belt and Road Initiative - World Bank (World Bank, Washington, DC, 2020)
This study provides a comprehensive comparative analysis of the business environment in six South Asian countries, Afghanistan, Bangladesh, India, Nepal, Pakistan, and Sri Lanka, to examine whether business regulatory requirements in these countries hinder them from fully benefiting from BRI project spillovers. The analysis is based on available secondary data sources and responses to a structured questionnaire sent to selected private sector participants in each of these countries, eliciting information on the law, regulation, and practice in a wide range of thematic areas influencing the overall business and regulatory environment. Survey respondents identified nine key themes as the most challenging for the private sector, including from the perspective of potential benefits from BRI-induced opportunities. The thematic areas are: (a) licensing and inspection requirements; (b) regulations and practices governing foreign investment; (c) access to resources such as land, credit, and electricity; (d) regulatory restrictions on the operation of foreign firms, such as local content requirements and currency repatriation; (e) regulatory governance and corruption and state capture; (f) predictability and quality of the regulatory framework, especially corporate taxation; (g) government procurement laws and practice; (h) effective dispute settlement and grievance mechanisms; and (i) trade and customs regulations. The identified thematic areas promote connectivity and regional integration and thus are particularly relevant from the BRI perspective. Improvements along different dimensions of these thematic areas will likely enable countries in the region to gain from BRI-induced opportunities.